Effect of High Intensity Functional with Strategy Sports Training on Cognitive Performance for Physical Education Achievement in High School Students - Wandee, Amorntheap; Chabairam, Ban; Homjan, Suchart (Physical Education Theory and Methodology, 2023)
Study purpose. This research aims to develop cognitive performance on the success of sports skills in physical education in Buriram Province. Materials and methods. The sample group of 80 people was divided into 2 groups of 40 people each. The control group was taught a regular strategy of handball instruction. The experimental group was taught a strategy of handball instruction with high-intensity functional training. Both groups were taught for 1 hour per week according to the normal teaching schedule of the school for a period of 8 weeks. All students were assessed by a computerized cognitive test battery and Sports skills achievement test in pre- and post-experimental. Analysis of the research data was performed by testing differences between the groups using the parametric and non-parametric statistics. Results. After 8 weeks of the experiment, analysis of the difference between the experimental group and the control group in the experimental data was carried out showing that the cognitive performance in terms of attention, executive function, cognitive flexibility, and working memory takes less time in the experimental group than in the control group, including Sports skills achievement scores in the test where the experimental group had more scores than the control group, which is statistically significant at .05. Conclusions. High-intensity functional with strategy sports training program in physical education class can develop cognitive performance in terms of attention, executive functions, cognitive flexibility, and working memory in high school students.